LEARNING CHARACTER VALUE THROUGH INDONESIA’S LITERATURE MINANGKABAU’S LOCAL COLOR - Iswadi Bahardur (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Character is the absolutely of characteristic that human having. It is original and rooted in human personality. It can be better with knowledge and human understanding of kindness, desire to do goodness, and do good thing. The understanding of moral’s concept, moral’s attitude, and moral’s behavior are also involved. The understanding of them can be grown throw formal and informal of education, and also reading form. Entertaining reading form and has humanist value is a good way to support the learning of the good characteristic. In new modern Indonesian language context has happening moral’s critical that is shown by the increasing of deviant behavior, the rate of violence, crime, and widespread of pornography network. Because of that the Indonesian character development for young people especially is needed to be encouraged. To realize that purpose, literature is an alternative reading way which can be used. Literature, especially prose has usefulness aspect and entertaining that can persuade readers to learn characters values. In Indonesia’s literature Minangkabau’s Local Color especially, for example, can be learned some character values related to culture and Minangkabau custom. This paper has purpose to description some character of values that contain in Indonesia’s literature minangkabau’s local color, especially in Aa Navis’s short stories. His short stories is collected in Robohnya Surau Kami’s book is considered has a power to reflection the character of values that born in Minangkabau philosophy and can be used as the material learning by young people. Keywords: learning, short stories, philosophy, Indonesia’s literature minangkabau’s local color, character’s values.